(untitled) (Research, Society and Development, 2023)
Introduction: The security of institutional environments, which contain valuable assets, is often done by expensive proprietary hardware and software systems. Aiming to alleviate this problem, this article proposes an initial solution based on software development and use of free hardware, mostly open source, so that in the future it can be used to protect these environments. Our goal is to propose a Basic Hardware Prototype and a Web System using free technologies, aiming to propose a software and hardware base to generate security and door opening control in environments. Methodology: In this project, we researched the tools and technologies available for the creation of the Prototype and the Web System, the tools for development were defined, we created work plans for modeling, creation and development, and finally the work in the solution was put into practice using programming language. Results: We developed a Basic Hardware Prototype using the Arduino platform along with other accessory components in order to be able to communicate with the Web Software. This was initially modeled using a class diagram and later developed using the Grails framework with Groovy programming language, in addition to MySQL for data storage. This system contains developed web services that can be accessed by the prototype. With these artifacts produced, we were able to create a basic solution that will serve as an initial model for the implementation of a low-cost and more robust security system in the future.